Medical management of Rhodococcus equi infections: A clinical epidemiology perspective. (9th December 2020) - Huber, L.
Summary: Rhodococcus equi infections cause severe pulmonary disease in foals, affecting animal welfare and increasing production costs in horse‐breeding farms. Extra‐pulmonary disorders (EPD) are relatively common and can occur independently of pulmonary disease; foals with EPD have a more guarded prognosis. The accompanying paper by Shaw et al . (2021) reports the successful diagnosis and medical treatment of a large abdominal abscess caused by R. equi infection. The authors report on the benefits of using gallium maltolate, a semimetal compound with antimicrobial activity, in combination with traditional R. equi infection antimicrobial treatment (combination of a macrolide and rifampicin). Experimental studies are needed to understand further the benefits of this combined therapy, to evaluate the synergistic effects and if it improves the concentration of antimicrobial drugs into infected tissues. The publication of this case report in Equine Veterinary Education is of clinical importance to equine practitioners when diagnosing and treating R. equi infected foals with or without EPD.